2017
DOI: 10.1111/1471-0307.12382
|View full text |Cite
|
Sign up to set email alerts
|

Recent aflatoxin survey data in milk and milk products: A review

Abstract: Aflatoxin M1 (AFM1) occurrence in human and animal milk, infant formula, powdered milk, cheese and yoghurt represents a risk for health. The last four years (2010–2014) of data, as well as the most frequently and updated analytical methods applied for AFM1 quantification, are evaluated. Aflatoxin B1, considered the most potent toxic aflatoxin, is metabolised to form the monohydroxy derivative AFM1. This metabolized, expressed in the milk, is relatively stable, and it is not eliminated by heat treatments or pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 112 publications
1
66
0
2
Order By: Relevance
“…1 The relationship between milk type and levels of AFM 1 was found to be significant at (P < 0.01). The level of AFM 1 contamination in milk and dairy products may depend on many factors, such as geographical location, seasonal effects and milk type [28]. Based on our results, the mean value of AFM 1 contamination was found to be 19.54 ng/L in all milk samples.…”
Section: Discussionmentioning
confidence: 55%
“…1 The relationship between milk type and levels of AFM 1 was found to be significant at (P < 0.01). The level of AFM 1 contamination in milk and dairy products may depend on many factors, such as geographical location, seasonal effects and milk type [28]. Based on our results, the mean value of AFM 1 contamination was found to be 19.54 ng/L in all milk samples.…”
Section: Discussionmentioning
confidence: 55%
“…Numerous researchers from different countries have indicated that AFM1 causes various health risk when people consume MDPs (Li et al, 2017;Ketney et al, 2017). Mean AFM1 levels in raw milk samples from Bosnia and Herzegovina and Croatia are 6.22 ng/kg and 5.65 ng/kg, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of this study reporting that AFM1 levels of 40.0% of the samples range from 2.46 to 35.00 ng/kg. AFM1 levels vary according to various elements such as region, season, cheese-making procedures, analytical method and conditions of cheese ripening (Fallah et al, 2009;Ketney et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[5]. This metabolite is thermally resistant and is not completely inactivated after pasteurization, sterilization, or other milk treatment processes, and thus could represent a public health concern [6]. Consequently, the Commission Regulation (EC), No.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this purpose, analytical methods must provide enough sensibility to reach the maximum limits that have been set by the Commission Regulation. In this sense, liquid chromatography mass spectrometry (LC-MS) methods, for multi-mycotoxin analysis in milk, have been reported in the literature [6,22,23]. In recent years, there has been increasing interest in evaluating the capability of the high-resolution mass spectrometry (HRMS) for multi-mycotoxin analysis because it provides not only a high resolution and accuracy mass results, but also a high sensibility and complementary structural information when compared with other MS detectors [21,24].…”
Section: Introductionmentioning
confidence: 99%